IMPLEMENTATION OF MIND MAPPING-ASSISTED PROBLEM-BASED LEARNING MODEL TO IMPROVE SOCIAL SCIENCE LEARNING OUTCOMES FOR STUDENTS AT CLASS 5B OF SD KRISTEN 03 EBEN HAEZER SALATIGA - Dyah Astiningtyas; Krisma Widi Wardani; Ria Triastuti (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
This paper discusses the implementation of the mind mapping-assisted problem based learning model in improving Social Science learning outcomes for students at grade 5B students of SD Kristen 03 Eben Haezer Salatiga. The method used in the classroom action research was carried out in two cycles with a number of 26 students in grade 5B of SD Kristen 03 Eben Haezer Salatiga. Data were collected using values from post-tests from each cycle to find out or test using the implementation of the problem-based learning model assisted by mind mapping to improve social science learning outcomes for students at grade 5B of SD Kristen 03 Eben Haezer Salatiga and uses observation sheets of teacher’s activities and students’ activities to determine the implementation of the mind mapping-assisted problem-based learning model that during teaching and learning process in the classroom. There is an increasing percentage of students who completed the preliminary implementation of 8 students with a percentage of 30.77% who completed and increased to 12 students with a percentage of 46.15% who completed the first cycle. In addition, it increased to 21 students with a percentage of 80.1% who completed the second cycle. The results are based on the whole students. Therefore, the implementation of the PBL learning model assisted by Mind Mapping has been proven to be able to improve students’ learning outcomes and has achieved the indicators with 80% of students who achieved learning completeness.